Regeneration of plants from apical meristem tips and nodal segments of Arachis pintoi - Rey de Badaró, Hebe Yolanda (2003)
The in vitro regeneration potential of shoot apical tips (2 to 3 mm in length), meristems (0.3 to 0.5 mm in length), and nodal segments (4 to 7 mm long with an axillary bud) of diploid (2n = 2x = 20) and triploid (2n = 3x = 30) cytotypes of Arachis pintoi was evaluated. Explants were cultured on MS medium supplemented with different concentrations and combinations of naphthaleneacetic acid (NAA) and benzyladenine (BA). In one experiment the effect of gibberellic acid was tested. The cultures were done in liquid and solid media. Plant regeneration can be readily achieved from all explants in one step of 30 d culture on MS + 0.01 mg/L each of NAA and BA or two steps consisting of 1) shoots regeneration through culture of explants on MS + 0.01 mg/L each of NAA and BA, and 2) induction of rooting in regenerated shoots by reculture on MS + 0.01 mg/L NAA. The plantlets were successfully transferred to pots in a greenhouse.